Meaning and moral order : explorations in cultural analysis - Wuthnow, Robert (University of California Press, 1989)
Meaning and Moral Order goes beyond classical, neoclassical, and poststructural theories of culture in its attempt to move away from problems of meaning to a more objective concept of culture. Innovative, controversial, challenging, it will compel scholars to rethink many of the assumptions on which the study of ideology, ritual, religion, science, and culture have been based.
Keywords: Culture.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; SOCIAL SCIENCE -- Sociology -- General.; Culture; Cultuursociologie.; Cultuur.; Zingeving.; Moraal.